Development of a Socio-Scientific Issues-Based Module on Chemical Equilibrium to Enhance Students' Critical Thinking and Learning Autonomy - Lestari Anggriani; Radjawali Usman Rery; Jimmi Copriady (STAI Hubbulwathan Duri, 2024)
This study aimed to develop and validate socio-scientific issue-based modules on chemical equilibrium to enhance students' autonomy and critical thinking skills. The research employed the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model within a Research and Development (RD) framework. Data were collected through interviews, surveys, validation sheets, and user response questionnaires. The module underwent validation by three experts, small-scale testing with three students of varying abilities, and user feedback from one teacher and 20 students across three schools (SMAN 1 Pinggir, SMAN 5 Pinggir, and SMAN 8 Mandau). Large-scale testing utilized a pretest-posttest control group design with 34 students from SMAN 8 Mandau to evaluate effectiveness. The module achieved a 92% validation score, reflecting high validity. Small-scale testing prompted minor revisions, and feedback from teachers and students was highly positive, with satisfaction scores of 100% and 90%, respectively. Large-scale testing showed significant improvements in the experimental group’s autonomy and critical thinking skills, with a high N-Gain of 0.71 for critical thinking and a moderate N-Gain of 0.64 for autonomy. In contrast, the control group achieved only moderate (0.50) and low (0.10) N-Gain scores, respectively. The findings underscore the effectiveness of socio-scientific issue-based modules in fostering critical thinking and autonomy, especially in complex scientific contexts. The study demonstrates that such modules are highly effective tools for enhancing higher-order thinking and engagement in scientific topics like chemical equilibrium. Further research could explore broader implementation across diverse educational settings.